The Role of Greenpeace Indonesia in Managing Air Pollution in Jakarta Through 2017-2019 - Hady Ho Al- Hakim; Made Fitri Maya Padmi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
One of the various environmental problems that often occur in big cities is air pollution.  This problem occurs because of the increasing volume of pollutant substances produced from daily activities. The air that has been polluted by pollutant substances not only affects human health, but also affects living things and the environment which will also be damaged by the pollution. Therefore, various solutions, especially the role of international organizations, are certainly needed to deal with these problems.  Greenpeace is one of the non-Governmental organizations. This environmental organization focuses on research related to pollution and air pollution in the city of Jakarta based on the argument that the air in Jakarta, which has been contaminated by various chemicals, is very dangerous if it is continuously inhaled by human. Air pollution certainly has a big impact on human health and other living things. For example, the emergence of diseases that occur due to lack of clean air that is inhaled resulting in a lack of oxygen in humans and other living things. Greenpeace monitoring of environmental problems that occur in the city of Jakarta has shown that Air pollution is at the health threshold level issued by WHO and exceeds the threshold level of the National Ambient Air Quality Standard. The role of Greenpeace is very important in dealing with pollution and air pollution in the city of Jakarta.